Understanding baffle overloads observed in high-mirror configuration on Wendelstein 7-X. (3rd August 2020) - Gao, Yu; Feng, Yuhe; Jakubowski, Marcin W.; Geiger, Joachim; Endler, Michael; Dhard, Chandra Prakash; Biedermann, Christoph; Naujoks, Dirk; Sunn Pedersen, Thomas; König, Ralf; Drewelow, Peter; Pisano, Fabio; et al.
Abstract: The operational regimes in the first divertor campaign of W7-X were limited by unexpectedly high heat loads on certain baffle tiles. In the high-mirror configuration, a permanent hotspot on the baffle plate was detected by the thermographic system, which was further confirmed during the post-campaign inspections of the plasma-facing components. The maximum heat load on three baffle tiles reached about 4.5 MW m −2, which was almost an order of magnitude above its designed value of 0.5 MW m −2 . The paper presents a detailed analysis to understand how the baffle plate, which is originally designed to screen the recycling neutrals and is therefore hidden from the hot plasma, can receive such a high heat load - a level that is expected for target plates. Three main causes have been identified: 1) the three baffle tiles are radially only about 5 mm away from a main heat channel towards a target, which is much shorter than the radial power decay length of several centimeters derived from the thermographic measurements in this region; 2) the three baffle tiles are intersected with field-lines of about 30 m length, which are long enough to collect considerable amount of heat via cross-field transport; 3) the baffle tiles have locally large grazing angles. In addition, the analysis method shown in this paper is of general use to estimate the heat flows in shadow areas of targets and thus to evaluate heat loads on the potentially critical components occurring in these areas, especially required for the design of complex 3D divertors like the one in W7-X.